Comparative Characteristics of Tuberculosis and Mycobacteriosis in Two Regions of the Russian Federation: Mari El Republic and Vladimir Region - E. N. Beloborodova; V. N. Zimina; E. I. Kulabukhova; Т. A. Kuznetsova; O. V. Fesenko (Туберкулез и болезни лёгких)
The objective: to study the regional prevalence of mycobacteriosis and the types of non-tuberculous mycobacteria causing mycobacteriosis in Mari El Republic and Vladimir Region, to conduct a comparative clinical and radiological analysis of mycobacteriosis and tuberculosis.Subjects and Methods. Cultures of non-tuberculous mycobacteria available in the bank of the bacteriological laboratory of two regions were analyzed: 182 cultures in the Republic of Mari El and 44 cultures in Vladimir Region. Medical records and X-ray archives of patients who were found to be positive for non-tuberculous mycobacteria were retrospectively studied.Results. The incidence of mycobacteriosis in Vladimir Region and Mari El Republic made 1.5 and 4.3 cases per 100,000 population, respectively. Cultures of non-tuberculous mycobacteria that caused mycobacteriosis belonged to diverse species, and M.avium-complex was the most common (76% of cases). There were no statistically significant differences in the location and extent of lesions in patients with mycobacteriosis and tuberculosis (p > 0.05). The frequency of positive results of Mantoux test with 2TU was comparable Positive results of TRA test were found significantly more often among patients with tuberculosis versus patients with mycobacteriosis (15/19 (78.9%) and 9/24 (37.5%), respectively; p < 0.05). However, this is insufficient for differential diagnosis of these diseases.